Human Capital and Funding Success: Evidence from an Indonesian Equity Crowdfunding - Kusumaningrum, Susana Diah; Risfandy, Tastaftiyan; Purnomowati, Nasyi'ah Hasanah; Hartomo, Deny Dwi (The Asian Journal of Technology Management (AJTM), 2023)
This study examines the impact of human capital on funding success in the context of Equity Crowdfunding (ECF) by analyzing data from 72 start-up companies seeking funding through SANTARA, the first ECF platform in Indonesia. Our findings indicate that various human capital indicators, including the number of directors, team members, economics undergraduate education, and graduates from foreign universities, do not significantly influence ECF success. However, we observed an intriguing result: start-up leaders with undergraduate degrees have a negative impact on crowdfunding success, leading to longer funding durations. This suggests that start-ups in Indonesia should not solely prioritize leaders with impressive educational backgrounds but should also consider individuals with practical experience in the business industry to enhance their chances of crowdfunding success.